Relações de poder nas fronteiras do império português: as correspondências do Marquês de Alegrete (1814-1818) - Medeiros, Clarissa Prestes (2015)
The following work was developed in the concentration area of “History, Culture and Power” in the research line of “Integration, Politics and Frontier” of the masters course of the Post Graduated Program in History of the Federal University of Santa Maria (UFSM), with support from CAPES scholarship. Its objective is to analize the administration trajectory of Marquess of Alegrete based on his oficial corespondences to establish his power relationship net, especially perceived during the initial period of his administration as Governor and Captain- General of the Capitania de São Pedro do Rio Grande do Sul (1841-1818), for a better comprehention on the functioning of the portuguese administration on the frontier of its Empire. In this study there were analized exclusively letters sent to the Capitania authorities by Marquess of Alegrete along the years of 1814 to 1818, which were divided in two moments: from 1814 to 1815, that comprise the initial years of the administration; and the years of 1816 to 1818, in which the Capitania was in war and the end of his mandate. From it, it was possible to determine that the Marquess of Alegrete was appointed to the Capitania of São Pedro of Rio Grande do Sul intending to establish in this territory an administration molded on portuguese manners, in addition to protect the southern border of the empire, even with expansionists purposes. The Marquess sought to attend to this task by approaching powerful men from the region, firming with them relations to best fufill the objectives set to the Capitania and, therefore, established a large social net that was fundamental to his success as a Marquess in the accomplishment of the objectives that the Coroa portuguesa determined to the Capitania of São Pedro of Rio Grande do Sul